A qualitative exploration of experiences of others and accounts of self in the narratives of persons who have experienced traumatic brain injury - Du Preez, Elizabeth (University of Pretoria, 2013)
Dissertation (MA (Counselling Psychology))--University of Pretoria, 2007.